Reta graduada: um registro de representação dos números racionais - Silva, Marcelo Cordeiro da (2008)
This present study aimed to introduce the rational numbers concept on Elementary School. This study is about semiotic approach education, based on representation s register theory by Raymond Duval (1993, 1995, 2005), found on article by French research Adjiage and Pluvinage (2000). In this article has proposed to consider the graduated straight line as a register of semiotic representation of rationals numbers, it indicates good results to education comparing to use of geometric figures dimension size 2, as chocolate bars, for example. Two questions guided this study: if the introduction of graduated straight line as a semiotic register to rationals numbers extends the possibility in opposition of difficulties to learn rationals numbers, and if it setups as element to help on Brazilian education. The dates for this analyze were Parâmetros Curriculares Nacionais para o Ensino Fundamental (PCN) to 2nd cycle (3rd and 4th grades) and 3rd cycle (5th and 6th grades) and the volumes of a didactic books' collection to these grades. We could check that the graduated straight line's or geometric s register has potential that could to promote education because it designs as a true semiotic register with a lot of signs and adaptable to development of a set of skills. This approach isn't recommendation by PCN and it doesn't act in didactics books, in this case, we can infer that if it could be introduced among us it can be a element to help on Brazilian education